Review paper on fatigue behavior of reinforced concrete beams. (2020) - Dineshkumar, R.; Ramkumar, S.
Abstract: Fatigue is a progressive brittle failure of a structural element under repeated, cyclic or fluctuating loads, which may reduce the life of structures. This paper gives a comprehensive information about the fatigue behavior of reinforced concrete beam with mineral admixtures. The fatigue behavior of reinforced concrete beam depends on the size of the beams, support conditions, number of fatigue cycles, loading limits, frequency and amplitude of loading applied. The influence of mineral admixtures in fatigue life of structure with respect to the relationship between the number of fatigue cycles and the stress developed in the beam due to fatigue loading.